2011
DOI: 10.1016/j.ydbio.2011.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Membrane extensions are associated with proper anterior migration of muscle cells during Caenorhabditis elegans embryogenesis

Abstract: C. elegans body wall muscle is formed after a series of well-orchestrated steps. With the onset of specification embryonic muscle cells accumulate under the hypodermal seam cells at the left and right sides of the embryo. Shortly thereafter they begin to migrate dorsally and ventrally resting beneath the dorsal and ventral hypodermis eventually forming the four muscle quadrants present upon hatching. In this study we describe the plasma membrane dynamics of these migrating cells and observe the extension of fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 63 publications
1
14
0
Order By: Relevance
“…Several genes have been found to disrupt ventral and anterior migration of BWMs, including lam-1 and -2 encoding laminin subunits and vab-2 encoding an ephrin ligand (Viveiros et al, 2011). Using parental injection RNAi and F1 animal expressions assays, we confirmed that hypomorphic function of lam-2 resulted in UNC-120-positive BWMs that failed to migrate properly by the 1.5-fold stage of embryogenesis, occupying positions that were more posterior and dorsal compared to wild type controls (Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…Several genes have been found to disrupt ventral and anterior migration of BWMs, including lam-1 and -2 encoding laminin subunits and vab-2 encoding an ephrin ligand (Viveiros et al, 2011). Using parental injection RNAi and F1 animal expressions assays, we confirmed that hypomorphic function of lam-2 resulted in UNC-120-positive BWMs that failed to migrate properly by the 1.5-fold stage of embryogenesis, occupying positions that were more posterior and dorsal compared to wild type controls (Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…Rather, we propose that preferential association of PGCs with endodermal cells may reflect differences in the relative stability of adhesive interactions that endodermal cells and mesodermal cells make with their neighbors. Mesodermal cells are highly mobile as they ingress from the ventral surface and in many cases migrate extensively within the embryo (Schnabel et al, 1997;Viveiros et al, 2011). Therefore, mesodermal cells behave like mesenchymal cells and must be able to make and break new contacts rapidly; by contrast, endodermal cells remain as a unified cell group (Schnabel et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…C. elegans has four ephrins, vab-2/efn-1, efn-2, efn-3, efn-4, and one ephrin receptor, vab-1 (George et al 1998;Chin-Sang et al 1999;Wang et al 1999). Eph signaling has pleiotropic functions in C. elegans development, including (but not limited to) epidermal morphogenesis (George et al 1998;Chin-Sang et al 1999;Wang et al 1999) and muscle cell migration (Tucker and Han 2008;Viveiros et al 2011). Ephrins also have several documented functions in axonal navigation.…”
Section: Receptors and Adhesion Moleculesmentioning
confidence: 99%